Corporate Social Responsibility beyond Law: Preliminary Instances during COVID-19: Array - Ngwakwe, Collins (Acta Universitatis Danubius. Juridica, 2020)
A new wave of corporate social responsibility is emerging during the COVID-19 pandemic, which deserves research attention. Objective: the objective of this research is to present a preliminary instances of corporate social responsibility beyond law in the midst of COVID-19 pandemic. Prior work: the paper is inclined on the stakeholder theory of corporate responsibility. Approach: the paper applied a qualitative conceptual review and document analysis of information from the World Economic Forum on corporate social responsibility during the COVID-19 pandemic. Results: pandemic can instil altruistic corporate social responsibility beyond what the law may prescribe; such can alleviate humanitarian crisis and elevate corporate image. The corporate may not often be an infinitely capitalist prone entity, it can be empathic and altruistic under certain unexpected conditions such disease pandemic. Implications: corporate social responsibility beyond law has the potential to upgrade corporate image and social asset. Policy makers may save certain costs of enforcing social reasonability compliance by appealing to the conscience of the corporate. Value: this paper fills the gap in the literature regarding how and when the corporate can play the role of striving to carter for the poor during times of pandemic – a beyond law altruistic social responsibility.